Client and staff perceptions of the integration of trauma informed care and specialist posttraumatic stress disorder treatment in residential treatment facilities for substance use: A qualitative study. (6th September 2022) - Mefodeva, Valeriya; Carlyle, Molly; Walter, Zoe; Hides, Leanne
Abstract: Introduction: Comorbid posttraumatic stress disorder (PTSD) is prevalent among people seeking residential treatment for substance use disorders (SUD). We examined client and staff perceptions of the relationship between trauma and SUDs, and the integration of trauma‐informed care (TIC) and specialist‐delivered treatment for PTSD in residential alcohol and other drug (AOD) treatment facilities. Methods: Individual semi‐structured interviews were conducted with frontline staff ( n  = 20) and clients ( n  = 18) in two residential AOD treatment facilities in Queensland, Australia. Interviews were audio recorded, transcribed and shared client and staff data was analysed using thematic analysis. Results: Major staff and client themes emerged: PTSD was perceived as an underlying cause of SUD, where AOD is used to cope with and avoid PTSD and related symptoms (Theme 1). Residential facilities were perceived to provide a safe and supportive environment for clients (Theme 2). Psychoeducation on SUD and PTSD was also highlighted to normalise experiences associated with comorbid SUD/PTSD and promote help‐seeking pathways for specialist PTSD treatment. Concurrent treatment of SUD and PTSD in the residential setting was sought after and was perceived to enhance treatment outcomes (Theme 3). Staff saw the need for implementing TIC into the organisation and perceived TIC as a multi‐faceted and consistent approach of service delivery. Discussion and Conclusions: Both clients and staff perceive comorbid SUD/PTSD as a challenge in residential treatment, that may be overcome through integrating TIC and PTSD treatment in residential treatment facilitates for substance use. Organisational and practical implications are discussed.